Is Ultrasound Elastography Useful in Predicting Clinically Relevant Pancreatic Fistula After Pancreatic Resection?: A Systematic Review and Meta-analysis. Issue 10 (November 2020) - Marasco, Giovanni; Ricci, Claudio; Buttitta, Francesco; Dajti, Elton; Ravaioli, Federico; Ingaldi, Carlo; Alberici, Laura; Serra, Carla; Festi, Davide; Colecchia, Antonio; Casadei, Riccardo
Abstract : Objectives: Ultrasound (US) elastography has been proposed for the non-invasive prediction of clinically relevant pancreatic fistula (CR-POPF) in patients undergoing pancreatic resection. We aimed to perform a systematic review with meta-analysis to assess the diagnostic value of US elastography in predicting CR-POPF. Methods: MEDLINE via PubMed, Ovid Embase, Scopus, and Cochrane Library databases, and abstracts of international conference proceedings were searched up to April 20, 2020. Studies assessing the performance of abdominal US elastography in predicting CR-POPF in patients undergoing pancreatic resection were included. The quality of the studies was assessed using Quality Assessment of Diagnostic Accuracy Studies. Results: Five studies, including 247 patients who underwent partial pancreatic resection of whom 72 patients experiencing CR-POPF, were selected. All studies performed US elastography in different pancreatic sites. The pooled mean strain value was lower in pancreatic segments of patients experiencing CR-POPF than in those without, with a pooled weighted mean difference of −0.187 (95% confidence intervals, −0.303 to −0.071; P = 0.002). There was low heterogeneity between studies (I 2 = 7.6%), and all studies were at "high risk" or "unclear risk" of bias. Conclusions: This study provides evidence that US elastography values are statistically significantly lower in patients experiencing CR-POPF. Abstract : Supplemental digital content is available in the text.